5n-7=3n+16

Simple and best practice solution for 5n-7=3n+16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5n-7=3n+16 equation:


Simplifying
5n + -7 = 3n + 16

Reorder the terms:
-7 + 5n = 3n + 16

Reorder the terms:
-7 + 5n = 16 + 3n

Solving
-7 + 5n = 16 + 3n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-3n' to each side of the equation.
-7 + 5n + -3n = 16 + 3n + -3n

Combine like terms: 5n + -3n = 2n
-7 + 2n = 16 + 3n + -3n

Combine like terms: 3n + -3n = 0
-7 + 2n = 16 + 0
-7 + 2n = 16

Add '7' to each side of the equation.
-7 + 7 + 2n = 16 + 7

Combine like terms: -7 + 7 = 0
0 + 2n = 16 + 7
2n = 16 + 7

Combine like terms: 16 + 7 = 23
2n = 23

Divide each side by '2'.
n = 11.5

Simplifying
n = 11.5

See similar equations:

| w(4w+6)+2w=2(2w^2+7w-3) | | -2q-58=2-4 | | 6+5m=8m | | x^2+33x+37=0 | | 13-4x=6x-2 | | -(7y+4)-(-6y-8)=0 | | 4+3=0 | | 7-9=-15+-9q | | 2x^2-11x=1 | | 25y^2-15y=5y | | 6x+6=126+6x | | 12(3x-1)=3(12x+2) | | 177-6x=39x+17 | | 12y^2-27=0 | | 8+5r-7=9r+9-6r | | 8x-35=25-2x | | 8-8x=133-43x | | 3x+17=13x-83 | | 7(t^2+5t-9)+t=t(7t-2)+13 | | 4t=-44 | | -7x+6=90 | | 3x+17=7x+3 | | 9x+5x-2x=0 | | 4=0.5(3x-4) | | 10x-15=-5x+30 | | 5s+11s=80 | | 115-5x=5x+15 | | 8+5y=-27 | | 3x^2-13x-16=-6 | | 0.05(x+30)-0.02(x-10)=3.2 | | -4586+y=5876 | | -9(3b+1)+(28b-2)=0 |

Equations solver categories